Media Games in the Background of Slovak Parliamentary Elections in 2016 - Peter Horváth; Matúš Meluš (Communication Today, 2025)
Our analysis deals with the electoral contest of individual political parties both before and after the 2016 Slovak parliamentary election was held. The space, which is provided from all kinds of media to political parties, is various. Each medium has an owner and each owner supports different interests. Parliamentary election is considered to be the most important election in Slovakia and thanks to that really wide media coverage is given to them. A couple of months before the opening of the polling stations, discussions had already been underway in both professional and amateur circles regarding the possible variations of the next governing political parties. The media play a large part in decision-making because they can have a meaningful influence on public opinion. Many voters today decide who they will vote for according to media coverage. Political programmes and agendas of the parties and political representatives come second in this decision. In our analysis we also look at online social networking sites, which are currently a huge phenomenon. Every political subject nowadays has its own website and every modern politician has a profile page on Facebook, an account on Twitter and on other social networks. We will also try to approach the possible perspectives of the development of the Slovak political scene.